2015
DOI: 10.14814/phy2.12588
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet-induced programing of gut taste receptor and inflammatory gene expression in rat offspring is ameliorated by CLA supplementation

Abstract: Consumption of a high-fat (HF) diet during pregnancy and lactation influences later life predisposition to obesity and cardiometabolic disease in offspring. The mechanisms underlying this phenomenon remain poorly defined, but one potential target that has received scant attention and is likely pivotal to disease progression is that of the gut. The present study examined the effects of maternal supplementation with the anti-inflammatory lipid, conjugated linoleic acid (CLA), on offspring metabolic profile and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…TAS1R1 and TAS1R3 form a heterodimer which detects umami taste, and TAS1R3 can also form a heterodimer with TAS1R2 to detect sweet taste ( 55 , 56 ). We were recently the first to report that offspring at weaning from HF-fed mothers have increased expression of Tas1r1 and reduced expression of Tas1r3 in the gut compared with offspring from CD mothers ( 57 ). In line with these findings, there was a significant interaction between maternal HF and salt on gut Tas1r1 expression in the gut of adult male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…TAS1R1 and TAS1R3 form a heterodimer which detects umami taste, and TAS1R3 can also form a heterodimer with TAS1R2 to detect sweet taste ( 55 , 56 ). We were recently the first to report that offspring at weaning from HF-fed mothers have increased expression of Tas1r1 and reduced expression of Tas1r3 in the gut compared with offspring from CD mothers ( 57 ). In line with these findings, there was a significant interaction between maternal HF and salt on gut Tas1r1 expression in the gut of adult male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that a MO diet leads to early onset of puberty in male and female offspring that is associated with increased weight at weaning, hyperleptinemia and increased fat mass in the immediate pre-pubertal period. [29][30][31][32] In the current…”
Section: Discussionmentioning
confidence: 99%
“…A lower level of linoleic acid reported before in RA serum is consistent with our results in CIA [ 34 ]. Linoleic acid also has the potential to ameliorate the high expression level of NLRP3 genes and reduced the release of mature IL-1β and other cytokines [ 35 , 36 ]. Despite that methotrexate could damage the dietary absorption of linoleic acid [ 37 ], it had already been reported to increase linoleic acid in carcinoma cell and was demonstrated in present study in CIA rats to play its anti-inflammation role [ 38 ].…”
Section: Discussionmentioning
confidence: 99%